Influence of Low-Temperature Charge on the Mechanical Integrity Behavior of 18650 Lithium-Ion Battery Cells Subject to Lateral Compression - Gao, Zhenhai; Zhang, Xiaoting; Xiao, Yang; Gao, Hao; Wang, Huiyuan; Piao, Changhao (Energies (Basel), 2019)
The study on the damage tolerance and failure mechanism of lithium-ion batteries (LIBs) subject to mechanical attack has attracted considerable attention. The electrochemical performance and thermal behavior of LIB were significantly affected by operation temperature and charging rate, but the dependence of these two factors on mechanical response remains unclear. Hence, we investigated how the environmental temperatures and rates in charging process affected the mechanical response characteristics of 18650 LIB cells. The onset of the short circuit in the cells which charged at temperatures above −25 °C occurred around their modulus peak under compression. At −25 °C, there was a strong possibility that a premature short circuit occurred locally in the cells during charging, thus they might show complex and variable mechanical response under compression. The failure moduli and crushing stresses of cells subject to compression tended to decrease as their ambient charging temperatures went down. Besides, 0.5 C-charged cells exhibited higher failure moduli and crushing stresses than the 1 C-charged cells above −20 °C. Morphology analyses of the cell electrode surfaces revealed that mossy lithium deposits became evident at temperatures below −10 °C. Furthermore, their distribution was uniform. Mechanical results also indicated that the short-term cycling at −20 °C and 0.5 C would soften the cell.